2016
DOI: 10.1038/aps.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin blocked enterohepatic circulation of diclofenac and alleviated NSAID-induced enteropathy in rats partly by inhibiting intestinal β-glucuronidase activity

Abstract: Aim: Diclofenac is a non-steroidal anti-inflammatory drug (NSAID), which may cause serious intestinal adverse reactions (enteropathy). In this study we investigated whether co-administration of ciprofloxacin affected the pharmacokinetics of diclofenac and diclofenacinduced enteropathy in rats. Methods: The pharmacokinetics of diclofenac was assessed in rats after receiving diclofenac (10 mg/kg, ig, or 5 mg/kg, iv), with or without ciprofloxacin (20 mg/kg, ig) co-administered. After receiving 6 oral doses or 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Moreover, at 100 mg/kg doses, oral treatment with glycyrrhizinic acid or intraperitoneal treatment with 18b-glycyrrhetinic acid, protected the hepatocytes of male Wistar rats against CCl 4 -induced liver injury evident by the significant reduction in AST, ALT and LDH levels compared to CCl 4controls. Intraperitoneal administration of glycyrrhizinic acid also did not provide hepatoprotection akin to tectoridin (43). In addition, structurally similar emodinol (46), isolated from the roots of perennial herb Paeonia Emodi showed stronger E. coli bGLU inhibition in vitro with IC 50 ¼ 63 mM compared to 18b-glycyrrhetinic acid [152].…”
Section: Terpenoids and Steroidsmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, at 100 mg/kg doses, oral treatment with glycyrrhizinic acid or intraperitoneal treatment with 18b-glycyrrhetinic acid, protected the hepatocytes of male Wistar rats against CCl 4 -induced liver injury evident by the significant reduction in AST, ALT and LDH levels compared to CCl 4controls. Intraperitoneal administration of glycyrrhizinic acid also did not provide hepatoprotection akin to tectoridin (43). In addition, structurally similar emodinol (46), isolated from the roots of perennial herb Paeonia Emodi showed stronger E. coli bGLU inhibition in vitro with IC 50 ¼ 63 mM compared to 18b-glycyrrhetinic acid [152].…”
Section: Terpenoids and Steroidsmentioning
confidence: 92%
“…Fascinatingly, structurally similar tectorigenin (42), an aglycone metabolite of 7-O-glycoside e tectoridin (43), isolated from the flowers of Pueraria thunbergiana, exhibited better inhibitory potency (IC 50 ¼ 0.30 mg/ml) than its congeners [150]. 50 mg/kg intraperitoneal pre-treatment of male ICR mice with tectorigenin or 100 mg/kg oral administration of tectoridin provided better hepatoprotection than dimethyl diphenyl bicarboxylate (DDB) and daidzein, by significantly lowering serum AST, ALT and LDH levels relative to CCl 4 -treated controls.…”
Section: Plant Extracts and Ethnomedicinal Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that the opposite regulation seemed to be associated with NF-jB pathways activation. [20,[32][33][34][35][36][37][38][39][40] Reports have showed that SCFAs such as butyrate suppresses NF-kappa B activation [32][33][34] via inhibiting deacetylases. Activation of NF-Kappa B has been reported to be associated with induction of P-gp expression.…”
Section: Parametersmentioning
confidence: 99%
“…[35][36][37][38] On the contrary, activation of NF-Kappa B has been reported to inhibit expression of Cyp3a. [20,39,40] However, the real mechanisms should be further investigated. Theoretically, the SCFA-induced upregulation of intestinal Cyp3a activity enhanced verapamil metabolism and decreased oral plasma exposure of verapamil.…”
Section: Parametersmentioning
confidence: 99%